2019
DOI: 10.2147/ijn.s208540
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nanodelivery and anticancer effect of a limonoid, nimbolide, in breast and pancreatic cancer cells</p>

Abstract: IntroductionNimbolide (Nim), a limonoid obtained from the neem tree, Azadirachta indica, has several pharmacological properties, including anticancer effects in different type of cancers. No drug-delivery system has been reported for enhancing the therapeutic application of this novel hydrophobic molecule.MethodsIn the present research, poly(lactic-co-glycolic acid) (PLGA) nanoparticles of Nim (Nim-nano) were formulated by nanoprecipitation, characterized for physicochemical properties, and screened for antica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Its incidence ranks tenth among malignant tumors, and its mortality ranks fourth among the causes of death from malignant tumors [8] . In recent years, more and more scholars have devoted themselves to researching anti‐pancreatic cancer drugs and confirmed that limonoids have certain anti‐pancreatic cancer activity [6,9–11] . Therefore, we also conducted research on the anti‐pancreatic cancer activity of the isolated limonoids in this study.…”
Section: Introductionmentioning
confidence: 82%
“…Its incidence ranks tenth among malignant tumors, and its mortality ranks fourth among the causes of death from malignant tumors [8] . In recent years, more and more scholars have devoted themselves to researching anti‐pancreatic cancer drugs and confirmed that limonoids have certain anti‐pancreatic cancer activity [6,9–11] . Therefore, we also conducted research on the anti‐pancreatic cancer activity of the isolated limonoids in this study.…”
Section: Introductionmentioning
confidence: 82%
“…Overall, the untargeted approach enabled the putative annotation of 279 compounds (excluding isobaric compounds), and the resulting dataset is reported in the Supplementary Materials, together with the relative abundance and mass spectra of each compound. The detected phytochemicals belonged to different chemical classes, such as flavonoids (108), limonoids/terpenoids (59), phenolic acids (49), lower-molecular-weight (LMW) phenolics (39), lignans (17) and stilbenes (7). In particular, anthocyanins (pigmented flavonoids) were primarily identified in T. ciliata, up to 104.16 mg Eq./g dry matter (Table 1) and mainly represented by cyanidin, pelargonidin, malvidin, peonidin, petunidin, delphinidin and their glycosides.…”
Section: Phytochemical Profiling Of Meliaceae Extracts Using Uhplc-qt...mentioning
confidence: 99%
“…For example, the Egyptian flaxseed, especially Giza-9, and its dietary formulations are enriched with lignans and exerted an in vitro and in vivo anticancer effect on a human breast cancer cell line and in mice bearing tumors [58]. Nanoformulated nimbolide, is characterized by its sustained release for more than 6 days in PBS (pH 7.4) and also exerted enhanced cytotoxicity about two-to three-fold in both breast and pancreatic cancer cell lines compared with free nimbolide [59].…”
Section: Pearson's Correlations Between Phytochemical Profile and Bio...mentioning
confidence: 99%
“…In many degenerative disorders including diabetes, and various types of cancers including pancreatic cancer, the potential of neem plant extract is considered to be due to the abundant presence of the active limonoid, azadirachtin. Azadirachtin and related limonoids have been shown to protect β-cells from oxidative and inflammatory stress-induced cytotoxicity by manipulating the cell signalling kinases and anti-inflammatory responses [ 24 , 25 , 26 , 27 , 28 ]. The present study focuses on the identification of biochemical markers in Rin-5F cells affected by LPS treatment and the mechanism of protection of cytotoxicity by AZD.…”
Section: Introductionmentioning
confidence: 99%